Nanocomposites: An In-Depth Exploration of Synthesis, Properties, Classification, and Prospective Application - Imo, F. U.; Nwabueze, C. A. (Darul Yasin Al Sys, 2025)
Rapid advances in artificial intelligence (AI) and materials engineering have expanded options for high-performance materials, with nanocomposites—heterogeneous hybrids formed by incorporating nanoscale constituents—offering distinctive property combinations driven by composition, structure, and interfacial interactions. This study’s objective is to synthesize current knowledge on how nanoscale constituents (e.g., nanofibers, nanoparticles, nanorods, nanotubes such as carbon nanotubes (CNTs), and graphene) modify mechanical, thermal, and electrical responses, and to highlight practical techniques for processing enhanced MBC, PBC, and CBC composites alongside procedures for efficient, result-oriented characterization. Methodologically, the work collates and organizes techniques and procedures reported in the literature, emphasizing processing routes and characterization protocols relevant to applications across sectors. Key findings indicate that the incorporation of nanomaterials—characterized by very high tensile strength and thermal/electrical conductivity and often eco-friendly attributes—tends to alter and improve composite performance; nanocomposites, as multiphase systems with one, two, or three dimensions on the order of 1 mm to 100 nm, are increasingly adopted from small- to large-scale industrial contexts including automobiles, construction, electronics, information technology, food packaging, and biomedicine. The study concludes that nanomaterial integration is a viable strategy for tailoring composite properties and enabling broader industrial deployment. The contribution and implication lie in consolidating processing techniques for enhanced MBC, PBC, and CBC systems, outlining characterization procedures that support reproducible evaluation, and mapping current and prospective application domains relevant to today’s technology landscape.